Manual on framework for river health assessment in Thailand - Shinde, Victor R.; Mukand S., Babel; Suttharom, Prangpisut (Asian Institute of Technology, 2018)
This manual has been developed by researchers from the Asian Institute of Technology (AIT) as part of project that sought to develop a river health assessment framework for Thailand. The project was supported by CGIAR’s Programme on Water, Land and Ecosystem (Greater Mekong) and Australian Aid. The authors of this Manual—Victor R. Shinde, Mukand S. Babel, and Prangpisut Suttharom—acknowledge the support provided by a number of organizations and individuals. These include the Pollution Control Department of Thailand, and Thai Water Partnership; and Oleg Shipin, Sangam Shrestha, Pinida Leelapanang Kamphaengthong, and Panpilai Sukhonthasindhu who were all part of the project. Special thanks also go to Kim Geheb and Mayvong Sayatham from the CGIAR WLE Programme for providing valuable insights during the course of the project. In early 2018, the project team presented this framework to an international group of scientists and practitioners from all over the world. Their feedback and input have helped fine-tune the content of this manual. The authors extend their sincere gratitude to these experts.